Applications of iron and nickel immobilized on hydroxyapatite‐core‐shell γ‐Fe2O3 as a nanomagnetic catalyst for the chemoselective oxidation of sulfides to sulfoxides under solvent‐free conditions. Issue 8 (23rd March 2018) - Sajjadifar, Sami; Rezayati, Sobhan; Arzehgar, Zeinab; Abbaspour, Sima; Torabi Jafroudi, Mogharab
Abstract : A heterogeneous iron and nickel immobilized on hydroxyapatitecore‐shell γ‐Fe2 O3 nanomagnetic catalyst has been prepared for selective oxidation of sulfides to sulfoxides in the presence of 30% H2 O2 . Abstract : In the present study, Fe 2+ and Ni 2+ immobilized on hydroxyapatite‐core‐shell γ‐Fe2 O3 (γ‐Fe2 O3 @HAp‐Fe 2+ and γ‐Fe2 O3 @HAp‐Ni 2+ ) with a high surface area has been synthesized and characterized by Fourier transform infrared (FTIR), X‐ray diffraction (XRD), vibrating sample magnetometer (VSM), transmission electron microscopy (TEM), and scanning electron microscope (SEM) techniques. Then, γ‐Fe2 O3 @HAp‐Fe 2+ and γ‐Fe2 O3 @HAp‐Ni 2+ were used as a new and magnetically recoverable nano catalyst for the selective oxidation of sulfides to sulfoxides with 33% aqueous H2 O2 (0.5 mL) as an oxidant at room temperature in good to excellent yields and short reaction time. Nontoxicity of reagent, mild reaction condition, inexpensive and high catalytic activity, simple experimental procedure, short period of conversion and excellent yields, and ease of recovery from the reaction mixture using an external magnet are the advantages of the present method.